Design and applications of photobioreactors - A review - Sirohi, Ranjna; Pandey, Ashutosh Kumar; Ranganathan, Panneerselvam; Singh, Shikhangi; Udayan, Aswathy; Kumar Awasthi, Mukesh; Hoang, Anh Tuan; Chaitanya Reddy, Chilakamarry; Kim, Sang Hyoun; Sim, Sangjun Jung (Elsevier Ltd, 2022)
There has been increasing attention in recent years on the use of photobioreactors for various biotechnological applications, especially for the cultivation of microalgae. Photobioreactors-based production of photosynthetic microorganisms furnish several advantages as minimising toxicity and providing improved conditions. However, the designing and scaling-up of photobioreactors (PBRs) remain a challenge. Due to huge capital investment and operating cost, there is a deficiency of suitable PBRs for development of photosynthetic microorganisms on large-scale. It is, therefore, highly desirable to understand the current state-of-the-art PBRs, their advantages and limitations so as to classify different PBRs as per their most suited applications. This review provides a holistic overview of the discreet features of diverse PBR designs and their purpose in microalgae growth and biohydrogen production and also summarizes the recent development in use of hybrid PBRs to increase their working efficiency and overall economics of their operation for the production of value-added products.